2015
DOI: 10.1007/s00216-014-8439-7
|View full text |Cite
|
Sign up to set email alerts
|

From individual proteins to proteomic samples: characterization of O-glycosylation sites in human chorionic gonadotropin and human-plasma proteins

Abstract: O-glycosylation-site characterization of individual glycoproteins is a major challenge because of the heterogeneity of O-glycan core structures. In proteomic studies, O-glycosylation-site analysis is even more difficult because of the complexity of the sample. In this work, we designed a rapid and convenient workflow for characterizing the O-glycosylation sites of individual proteins and the human-plasma proteome. A mixture of exoglycosidases was used to partially remove O-glycan chains and leave an N-acetylga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
15
1
3
Order By: Relevance
“…S6 ), 54 EEAP S LRPAPPPIS 67 , m / z 706.27 3+ ) indicates O -glycosylation at the site Ser 58 . This contrasts recent findings by Bai et al who reported the site Ser 67 to be O -glycosylated, but not the site Ser 58 ( 76 ). In agreement with previous findings, both fibrinogen O -glycopeptides ( 524 ST GK T FPG 531 , m / z 725.78 2+ , 54 EEAP S LRPAPPPIS 67 , m / z 706.27 3+ ), detected in the present study, were found to be decorated with monosialylated T-antigens.…”
Section: Resultscontrasting
confidence: 99%
“…S6 ), 54 EEAP S LRPAPPPIS 67 , m / z 706.27 3+ ) indicates O -glycosylation at the site Ser 58 . This contrasts recent findings by Bai et al who reported the site Ser 67 to be O -glycosylated, but not the site Ser 58 ( 76 ). In agreement with previous findings, both fibrinogen O -glycopeptides ( 524 ST GK T FPG 531 , m / z 725.78 2+ , 54 EEAP S LRPAPPPIS 67 , m / z 706.27 3+ ), detected in the present study, were found to be decorated with monosialylated T-antigens.…”
Section: Resultscontrasting
confidence: 99%
“…A human serum-specific N-linked peptide database that was generated using solid phase extraction of glycosite-containing peptides (SPEG)1137 and solid phase extraction of N-linked glycans and glycosite-containing peptides (NGAG)18 in previous studies was used. The O-linked peptide database was also from previous studies3839. A minimum of two oxonium ions in top 10% of peaks in the spectra was required in an MS/MS spectrum to qualify for glycopeptide search.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous O-glycosylation studies rely on lectin affinity isolation. Jacalin has been used for O-glycosylation characterization of fetal calf serum (25,92), human plasma (140) and serum (79). Peanut agglutinin has been used for characterization of protein O-glycosylation of human plasma, platelets and endothelial cells (26) yielding the largest data set for protein O-glycosylation to date.…”
Section: O-glycosylation Studiesmentioning
confidence: 99%